Overlooked non-motor symptoms in myasthenia gravis. Issue 9 (22nd November 2012) - Suzuki, Shigeaki; Utsugisawa, Kimiaki; Suzuki, Norihiro
Abstract : Patients with myasthenia gravis (MG) may have various non-motor symptoms in addition to fatigability and weakness of skeletal muscles. Thymomas contain abundant immature thymocytes and developing CD4 and CD8 T cells. Thymomas are found in 15–25% of patients with MG and are associated with severe symptoms. We suggest that non-motor symptoms are based on the autoimmune disorders probably owing to an abnormal T cell repertoire from thymomas. Using previously reported cases and cases from our multicentre cooperative study, we review the clinical characteristics of patients with thymoma-associated MG who have non-motor symptoms. CD8 T cell cytotoxicity against haematopoietic precursor cells in bone marrow and unidentified autoantigens in hair follicles lead to the development of pure red cell aplasia, immunodeficiency and alopecia areata. In contrast, neuromyotonia, limbic encephalitis, myocarditis and taste disorders are autoantibody-mediated disorders, as is MG. Autoantibodies to several types of voltage-gated potassium channels and the related molecules can evoke various neurological and cardiac disorders. About 25% of patients with thymoma-associated MG have at least one non-motor symptom. Non-motor symptoms affect many target organs and result in a broad spectrum of disease, ranging from the impairment of quality of life to lethal conditions. Since relatively little attention is paid to non-motor symptoms in patients with thymoma-associated MG, the symptoms may be overlooked by many physicians. Early diagnosis is important, since non-motor symptoms can be treatable. A complete understanding of non-motor symptoms is necessary for the management of patients with thymoma-associated MG.